Sócrates en 90 minutos - Strathern, Paul, 1940-; Padilla Villate, José Antonio; Strathern, Paul, 1940- (Tres Cantos, Madrid, España : Siglo XXI de España Editores, S.A., 2014)
Offers a brief profile of the classical Greek philosopher, describes the highlights of his teachings, and assesses the influence of his ideas.
Online resource; title from ePub title page (Digitalia, viewed June 28, 2017)
Keywords: Socrates; Philosophers -- Greece -- Biography; Philosophy, Ancient; Electronic books